Conventional and Contemporary Arabic Language Teaching Methods: A Comparative Analysis - Abdillah Mahbubi (Alsina : Journal of Arabic Studies, 2024)
This study compares conventional and contemporary Arabic language learning methods to analyze their effectiveness, assessment strategies, and integration in Indonesia's context of pesantren and madrasah. Using a literature review approach, this research examines conventional methods (grammar-translation, direct, audio-lingual) and contemporary methods (eclectic, communicative, technology-based). The findings reveal that conventional methods, dominant in pesantren, excel in building grammatical foundations and understanding classical texts but lack emphasis on practical communication skills. Conversely, contemporary methods, prevalent in madrasahs, enhance speaking and student engagement through technology and interactive activities, though they require robust infrastructure and teacher training. Assessment strategies range from written tests for conventional methods to project-based and online assessments for contemporary methods. An integrated model combining grammar-translation, communicative, and technology-based approaches is proposed to address diverse learner needs across beginner, intermediate, and advanced levels.